Community Banks in Chippewa County : Changes in Small-Business Lending After the Dodd-Frank Act - Lettner, Brian; Sebatka, David; Carroll, Wayne (My University, 2018)
Small businesses are a huge part of the economy of semi-rural communities in the Midwest, and those businesses often rely on small banks for financing. Research at the national level has raised concerns that mergers among community banks have caused a decline in small-business lending. In this project, we focus on the banking industry in Chippewa County as a case study. Using data from the Federal Deposit Insurance Corporation (FDIC) and Federal Financial Institutions Examination Council (FFIEC), our research examines community banking trends in Chippewa County and compares the results to national trends. We analyze financial statements, market share reports, call reports, and other financial documents to find financial health patterns of the commercial banks within the county. Our research shows that there have been numerous bank mergers in Chippewa County over the last twelve years. In this project, we examine the financial condition of banks that remained independent or were acquired in mergers and identify the effects of the mergers on small-business lending for community banks in the Chippewa County.
Color poster with text, charts, and graphs.
Keywords: Community banks; Dodd-Frank Wall Street Reform and Consumer Protection Act; Chippewa County (Wis.); Posters